Efektivitas Pre-Lecture Quiz untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Fitri, Nur Qomaril; Efkar, Tasviri; Sunyono, Sunyono (Jurnal Pendidikan MIPA, 2018)
Effectiveness of Pre-Lecture Quiz to Improving the Critical Thinking. This research was aimed to describe the effectiveness of Pre-Lecture Quiz to improving student’s critical thinking skill on Arrhenius acid-base topic. The research method used was quasi experimental with non-equivalen pretest-posttest control group design. The sample selection was done by cluster random sampling, and XI IPA 4 is obtained as experimental class and XI IPA 5 as control class. The effectiveness of Pre-Lecture Quiz was showed by the significant difference for average n-Gain of flexible thinking skill between the control and experiment class, for control class was 0.53 with middle categorize and for experiment class was 0.70 with high cateogorize. The conclusion of this research is effective Pre-Lecture Quiz and has a high effect size to improving the ability of critical thinking on Arrhenius acid-base topic.Keywords: critical thinking, Pre-Lecture Quiz, Arrhenius acid-base DOI: http://dx.doi.org/10.23960/jpmipa/v19i2.pp62-74